2019
DOI: 10.1108/tr-08-2018-0117
|View full text |Cite
|
Sign up to set email alerts
|

Telecommunication and tourism development: an island perspective

Abstract: Purpose This paper aims to investigate the availability and contribution of destinations’ telecommunication structure and development on tourism development for the case of the small island economy of Mauritius. Design/methodology/approach The research uses annual data from 1992 to 2017 in a dynamic econometric setting, namely, an autoregressive distributed lag model to take into account the time series properties of the data. Findings Analysis of the results showed that telecommunication has contributed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…It is worth indicating that academic research in this specific field is rare; thus, there are only very few similar studies to which we could compare and contrast the present study's findings. Although recent studies (i.e., Shehzad et al [53]; Seetanah [54]; Kumar and Kumar [55]; Adeola and Evans [56]; Lorente-Bayona et al [13]; Gholipour et al [57]) performed empirical examinations to explain ICT's influence on tourism economy from various perspectives, their focus was on ICTs' effect on international tourism arrivals or international tourism expenditure, not on the cultural and tourism industries' convergence. In other words, their findings demonstrated that ICTs have a positive influence on international tourism demand.…”
Section: Discussion Of Main Findings Conclusion and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth indicating that academic research in this specific field is rare; thus, there are only very few similar studies to which we could compare and contrast the present study's findings. Although recent studies (i.e., Shehzad et al [53]; Seetanah [54]; Kumar and Kumar [55]; Adeola and Evans [56]; Lorente-Bayona et al [13]; Gholipour et al [57]) performed empirical examinations to explain ICT's influence on tourism economy from various perspectives, their focus was on ICTs' effect on international tourism arrivals or international tourism expenditure, not on the cultural and tourism industries' convergence. In other words, their findings demonstrated that ICTs have a positive influence on international tourism demand.…”
Section: Discussion Of Main Findings Conclusion and Implicationsmentioning
confidence: 99%
“…It was indicated that the adoption of ICTs boosted tourism development, and consequently, economic growth. The study by Seetanah [54] employed the international tourism demand function and ARDL-ECM estimation to test the impact of telecommunications on tourism development in Mauritius. A positive correlation was found between them in both the short and long term.…”
Section: The Impact Of Icts On Tourism and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Reference [38] examined the accessibility and influence of a destination country"s telecommunication pattern and its progress on tourism growth in small island nations (1992-2017). The estimated results showed that telecommunications have contributed positively to tourism development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Jia et al (2019), in current years, technological development and internet networking have brought the advantage of monitoring methods and data collection through mobile application, online review, video investigation, comments and other resources. This revelation starts at the end of the 1970s through the founding of the computer reservation systems and continues in the late 1980s with global distribution systems and finally in the 1990s followed by the development of internet (Seetanah, 2019).…”
Section: Introductionmentioning
confidence: 99%